Theoretical Study of Influence of Some Material Parameters on Solar Cell Efficiency - Naser, Nabiel M.; Ismail, Haidar J.; Mawlud, Saman Q. (Science Journal of University of Zakho, 2013)
Silicon solar cells are prevailing types in the commercial market due to their stability, robustness and reliability. In this article, we explored the important controllable design parameters affecting the performance of the silicon p-n junction solar cells by using the computer program (Matlab scrip file). Through the simulation process we also determined the sensitivities of each parameter. Besides that, some hypothetical materials are also examined to explore the effect of band gap, doping process and thickness of n-layer. We have come out the optimum parameters to achieve the best performance of this type of cell. A simple one-diode model is used in order to predict how the performance Silicon solar cell changes its characteristics with doping process. It was found that the optimum doping concentration of the base from (1016- 1019) cm-3and optimal thickness of n-layer is about (10-100) µm for silicon solar cell.